2020
DOI: 10.3344/kjp.2020.33.4.378
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of a single injection of ultrasound-guided retrolaminar paravertebral block for breast surgery: a prospective, randomized, double-blinded study

Abstract: Background: The thoracic paravertebral block is an effective analgesic technique for postoperative pain management after breast surgery. The ultrasound-guided retrolaminar block (RLB) is a safer alternative to conventional paravertebral block. Thus, we assessed the analgesic efficacy of ultrasound-guided RLB for postoperative pain management after breast surgery. Methods: Patients requiring breast surgery were randomly allocated to group C (retrolaminar injection with saline) and group R (RLB with local anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…It was reported that the intraoperative use of remifentanil in breast surgery was higher in patients receiving retrolaminar injection with saline than that in patients receiving RLB with local anesthetic mixture. 25 In our study, we also found that RLB clearly reduced the perioperative consumption of remifentanil, which led to shorter retention time in the recovery room of patients in the RLB group. However, the difference in the cumulative amount of sufentanil, cumulative PAIC bolus at 24 and 48 hours, and the frequency of using remedial drugs might be the reason for which the proportion of PONV in patients in the RLB group was lower than that in patients in the LIA group.…”
Section: Discussionsupporting
confidence: 70%
“…It was reported that the intraoperative use of remifentanil in breast surgery was higher in patients receiving retrolaminar injection with saline than that in patients receiving RLB with local anesthetic mixture. 25 In our study, we also found that RLB clearly reduced the perioperative consumption of remifentanil, which led to shorter retention time in the recovery room of patients in the RLB group. However, the difference in the cumulative amount of sufentanil, cumulative PAIC bolus at 24 and 48 hours, and the frequency of using remedial drugs might be the reason for which the proportion of PONV in patients in the RLB group was lower than that in patients in the LIA group.…”
Section: Discussionsupporting
confidence: 70%
“…In a study involving breast surgery, RLB at T4 showed first analgesic request was at 4.8 (3.0–24) h when using 20 ml of a 0.375% levobupivacaine [ 6 ]. Another study in breast surgery using 20 ml of 0.5% ropivacaine at T7 reported duration of analgesia of up to 12 h, lower VAS from 4 to 12 h [ 7 ]. Different surgeries, levels of injection and no additives explained the different analgesic durations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound, reduces the risk of complications [ 5 ]. Until now, there have been insufficient studies on cervical RLB as an analgesic technique for neck surgeries, through it has been shown to provide effective analgesia in breast surgeries [ 6 , 7 ], rib fractures [ 8 ], and abdominal surgeries, such as retroperitoneal nephrectomy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although RLB can be performed without ultrasonography, ultrasound images allow for visualization of the needle, catheter and local anesthetic distribution. Some studies reported the application of RLB for chest wall surgery (16)(17)(18)(19).…”
Section: Original Articlementioning
confidence: 99%